Analisis Kadar Asam Salisilat Pada Bedak Tabur Yang Beredar Di Kota Makassar - Rahmawati Rahmawati; Anita Anita; Amaliyah Firdausa (Lontara Journal of Health Science and Technology, 2022)
Loose powder is a cosmetic preparation in the form of a fine, soft, homogeneous powder so that it is easy to apply to the skin with the content in it must be safe. Salicylic acid works as a keratolytic, comedolytic and as a bacteriostatic, opening clogged pores on the skin. The purpose of this study was to identify and determine the levels of salicylic acid contained in loose powder samples. This type of research is a laboratory observation with the object of research is loose powder. This research is descriptive using color test method and spectrophotometric method, as many as 10 samples of loose powder. The results showed that there were 9 samples that were negative or did not contain salicylic acid and 1 positive sample contained salicylic acid which was indicated by a purple color change with a salicylic acid content of 0.030%. Thus, it can be concluded that in 10 samples of loose powder, 9 samples were negative and 1 sample positive with a salicylic acid content of 0.030% not exceeding the 2% threshold that has been set in accordance with the Regulation of the Head of BPOM RI Number Hk.03.1.23.08. 11.07517 of 2011 concerning Technical Requirements for Cosmetic Ingredients. Keywords: loose powder, salicylic acid, color test, spectrophotometri